2019
DOI: 10.1021/acs.jpclett.9b02594
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Photoluminescence and Modified Blinking Statistics in Alumina-Encapsulated Zero-Dimensional Inorganic Perovskite Nanocrystals

Abstract: We demonstrate enhancement of the photoluminescence (PL) properties of individual zero-dimensional (0D) Cs 4 PbBr 6 perovskite nanocrystals (PNCs) upon encapsulation by alumina using an appropriately modified atomic layer deposition method. In addition to the increased PL intensity and improved long-term stability of encapsulated PNCs, our single-particle studies reveal substantial changes in the PL blinking statistics and the persistent appearance of the long-lived, "delayed" PL components. The blinking patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 50 publications
3
46
0
Order By: Relevance
“…[38] The second theory involving a vacancy-assisted PL emission was offered, which regarded the strong PL emission as due to the intrinsic nature of Cs 4 PbBr 6 , in which Br vacancies (in most cases), tribromide and interstitial hydroxyl served as radiative recombination centers. [32,[39][40][41][42][43][44][45] From DFT calculation results, it was found that i) Br vacancies had a small formation energy under Br-deficit conditions; ii) their transition level matched well with the emissive energy; iii) their electronic charge density was highly localized (Figure 3a,b). [29] Therefore, one could obtain Cs 4 PbBr 6 with stronger PL emission if more defects could be induced under extremely Br-poor conditions.…”
Section: D-networked Cs 4 Pbxmentioning
confidence: 99%
“…[38] The second theory involving a vacancy-assisted PL emission was offered, which regarded the strong PL emission as due to the intrinsic nature of Cs 4 PbBr 6 , in which Br vacancies (in most cases), tribromide and interstitial hydroxyl served as radiative recombination centers. [32,[39][40][41][42][43][44][45] From DFT calculation results, it was found that i) Br vacancies had a small formation energy under Br-deficit conditions; ii) their transition level matched well with the emissive energy; iii) their electronic charge density was highly localized (Figure 3a,b). [29] Therefore, one could obtain Cs 4 PbBr 6 with stronger PL emission if more defects could be induced under extremely Br-poor conditions.…”
Section: D-networked Cs 4 Pbxmentioning
confidence: 99%
“…[56] The blinking behavior in single perovskite QDs was ascribed to random charging/discharging of the quantum dot due to the presence of fast nonradiative Auger recombination driven by photo-assisted ionization, similar to the other semiconductor QDs, e.g., CdSe. [48,53] Using the same techniques of single-molecule spectroscopy and time-resolved spectroscopy, the fluorescence blinking has recently been investigated in MAPbBr 3 QDs, [57][58][59][60] CsPbBr 3 QDs, [61][62][63][64] 0D Cs 4 PbBr 6 , [65] MAPbI 3 QDs. [66] Mandal et al [67] observed blinking in inorganic perovskite CsPbBr 3 QDs.…”
Section: Fluorescence Intermittency In Single Perovskite Quantum Dot mentioning
confidence: 99%
“…The contradictory conclusion may attribute to the loss of surface ligands 88 or the replacement of QDs cations by metal precursor 69 . Thus, fine control of ALD reaction conditions is crucial in determining the performance of QDs 64 . High reaction temperature would strip surface ligands, and thus low temperature is essential to preserve PLQY during ALD processes 65 .…”
Section: (Iii) and (Iv)mentioning
confidence: 99%